Differentiated approach to hernioplasty of paraesophageal hernias - Ioffe, O. Y.; Tarasov, T. A.; Markulan, L. Y.; Bagirov, M. M. (General Surgery, 2024)
The results of surgical treatment of paraesophageal hernias indicate a high recurrence rate, from 15% to 66%, with an average follow‑up period of 12 to 40 months. The main options for repairing the defect of the esophageal hiatus in the presence of paraesophageal hernia are crurorraphy and mesh‑reinforced crurorraphy. Both methods have their own advantages and disadvantages. The criteria for choosing a method have not been specified. Objective — to develop a differentiated approach to the surgical treatment of paraesophageal hernias, taking into account the size of the esophageal hiatus, and to determine its effectiveness. Materials and methods. The study included 157 patients who were operated on for paraesophageal hernias. They were divided into two groups. The patients in both groups did not exhibit any statistically significant differences in terms of mean age, body mass index, sex ratio, type, frequency of complaints, or results of the endoscopic and radiological examination. In Group I, hiatoplasty was performed using crurorraphy (61 (38.9%) patients). In this group, the threshold values of the esophageal hiatus dimensions were calculated using the developed device and methodology, which allowed predicting hernia recurrence during the follow‑up period of up to 18 months. In Group II (96 (61.1%) patients), the hernioplasty technique (crurorraphy or mesh‑reinforced crurorraphy) was chosen on the basis of the obtained threshold values. Results. In Group I, the mean hiatal surface area was 86.8±18.2 mm2 (53 to 161 mm2) and the width of the esophageal hiatus was 29.3±3.3 mm (24 to 38 mm). In Group II, they were 95.6±23.2 mm2 (51 to 212 mm2) and 31.1±3.7 mm (24 to 43 mm), respectively. The threshold hiatal surface area, at which the probability of recurrence after crurorraphy was >50%, was 90 mm2 (AUC — 0.926 (95% confidence interval — 0.827—1.000), with a sensitivity and specificity of 87.5% and 97.8%, respectively. The width of the esophageal hiatus was measured at a cut‑off point of 32 mm (AUC — 0.864 (95% confidence interval — 0.733—0.995), with a sensitivity and specificity of 75.0% and 78.0%. In Group II, posterior crurorraphy was performed in the case of a hiatal surface area <90 mm2 and a distance between the crura diaphragmatis <32 mm. In other cases, mesh‑reinforced crurorraphy was conducted. The recurrence rate in Groups I and II was 26.2% and 7.3% (p=0.001). Conclusions. The device and methodology that have been developed are capable of measuring the dimensions (length, width, and area) of the esophageal hiatus intraoperatively. These measurements can be taken for the entire area within the esophageal hiatus contour, independent of its shape, even when using laparoscopic methods. The study found that there was a probability of recurrence after crurorraphy >50% when the threshold hiatal surface area was 90 mm2, and the width of the esophageal hiatus was 32 mm. A differentiated approach to hiatoplasty involves using crurorraphy for hiatal surface areas <90 mm2 or distances between the crura diaphragmatis <32 mm. For larger hiatal surface areas or widths, mesh‑reinforced crurorraphy is indicated. This approach has resulted in a significant reduction in the recurrence rate from 26.2% to 7.3% (p=0.001) and has prevented complications associated with the use of implants for up to 18 months after surgery.